The Influence of Individual Factors and Work Conditions with Nurse's Mental Workload Using Method Nasa-TLX Banggai District Health Center - Busura, Aldi; Mulasari, Surahma Asti; Kristanto, Agung (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2023)
Workload is the interaction between individuals and things that can burden someone in completing work. The workload is divided into physical and mental, where the workload is influenced by individual characteristics and external factors, task demands, and work environment. The prevalence of workload in the province of Central Sulawesi (50.9%) experienced work stress caused by excessive workload. Banggai Regency is one of the regions in the province of Central Sulawesi. The purpose of this study was to find out how individual characteristics and working conditions can affect the mental workload of nurses at the Banggai District Health Center. this study uses the chi-square method. The sample used in this study is a nurse who is actively working at the Banggai District Health Center. The number of samples used is 225 nurses. The sampling technique is the Slovin technique. The measuring tool used is a research questionnaire from NASA TLX. This questionnaire is used to measure the mental workload of nurses at the Banggai District Health Center. Data were analyzed by univariate and bivariate. The results of this study indicate that the mental workload of nurses in Banggai Regency is in the high category (70.2%). The results of the bivariate analysis found that there was a relationship between age, task demands, work environment and the mental workload of nurses at the Banggai District Health Center (p-value 0.000). There is no relationship between gender and the mental workload of nurses at the Banggai District Health Center. The results of the multivariate analysis of age and task demands have a positive effect on workload, while the work environment has a negative effect on workload. The work environment is the most dominant factor affecting the mental workload of nurses at the Banggai District Health Center